2011
DOI: 10.1093/infdis/jiq091
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV-1 and Herpes Simplex Virus Type 2 Infection on Lymphocyte and Dendritic Cell Density in Adult Foreskins from Rakai, Uganda

Abstract: The increased CD4(+) cellular density in the HIV-uninfected, HSV-2-infected men may help to explain why HSV-2-infected men are at increased risk of HIV acquisition. The absence of this increase in men coinfected with both HIV and HSV-2 is likely in part the result of the progressive loss of CD4(+) cells in HIV infection. Conversely, HIV and HSV-2 coinfection appears to synergistically increase CD8(+) T cell densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 26 publications
3
44
0
Order By: Relevance
“…Both incident and prevalent HSV-2 infection are associated with an increased risk of HIV acquisition (3), and CD4 ϩ T cells found at the sites of HSV lesions bear the HIV coreceptors CCR5 and CXCR4 (17,34). We found HSV-specific CD4 ϩ T cells that produce proinflammatory cytokines in response to HSV stimula- ϩ T cells from the asymptomatic biopsy specimen produce IFN-␥ in response to whole HSV-2 antigen.…”
Section: Discussionmentioning
confidence: 72%
“…Both incident and prevalent HSV-2 infection are associated with an increased risk of HIV acquisition (3), and CD4 ϩ T cells found at the sites of HSV lesions bear the HIV coreceptors CCR5 and CXCR4 (17,34). We found HSV-specific CD4 ϩ T cells that produce proinflammatory cytokines in response to HSV stimula- ϩ T cells from the asymptomatic biopsy specimen produce IFN-␥ in response to whole HSV-2 antigen.…”
Section: Discussionmentioning
confidence: 72%
“…HSV lesions are associated with persistent infiltrate of CD4 + and CD8 + T cells in the mucosa (21,38) and at nerve endings (38) that may contribute to a chronic inflammatory state in genital skin and mucosa. In support of this hypothesis, histopathologic studies of foreskin in HIV-seronegative men after adult circumcision have shown a higher concentration of CD4 + and CD8 + T cells in HSV-2-seropositive compared with HSV-2-seronegative men (39). Thus, even persons with established infection and a functional immune system can experience both subclinical genital HSV shedding and lesional recurrences, which suggests that the virus can evade even mature host immune responses.…”
Section: Introductionmentioning
confidence: 92%
“…Asymptomatic HSV-2 infection is also associated with T cell alterations in the genital mucosa (3,5,6), an increased expression of CD69 and CCR5 by endocervical CD4 + T cells (3), and increased CD4 + T cell density (7) and CCR5 expression by CD4 + T cells (6) in the foreskin. Because CCR5 + T cells are the primary target for sexually transmitted R5-tropic strains of HIV (8), this increased density of target cells in the genital mucosa may be an important contributor to the increased HIV susceptibility observed in asymptomatic HSV-2 infection.…”
mentioning
confidence: 99%